Because we love peace; we must know all those who strive to detract her - Ballesteros, Julio (Revista Universidad de Guayaquil, 1987)
The destroyers of Peace roam throughout the world, they are the "honest" murderers who walk around in suits and ties; There are so many that we will list the main ones, given that all of them are hidden in various organizations and sects; Thus we have the S.S., the MOON Sect, the C.I.A., ODESSA, the KLU-KLUX KLAN, the SUMMER LANGUAGE INSTITUTE, WORLD VISION and branches such as TRADITION, FAMILY AND PROPERTY; These and many others belong to the BLACK INTERNATIONAL; who have permanently murdered and currently carry out inconceivable crimes, which amount to millions of human lives, be they: young children, adults and elderly people.